Genetic Grouping of Nephropathogenic Avian Infectious Bronchitis Virus Isolated in Morocco - Bouqdaoui, M.El; Mhand, R.A.; Bouayoune, H.; Ennaji, M.M. (International Journal of Poultry Science, 2005)
Thirty Moroccan isolates of infectious bronchitis virus (IBV) recovered from unvaccinated broiler chickens flocks originated from different regions of Morocco between 1997 and 2002, and two references strains Massachusetts and 4/91 (vaccine strains) were classified by reverse transcriptase-polymerase chain reaction (RT-PCR) and restriction fragment length polymorphism (RFLP) analysis using two restriction enzymes Hae III and Alu1. RFLP patterns of the amplified S1 gene of IBV (1720 bp) digested by two restriction enzymes HaeIII and Alu1 showed that Moroccan isolates of IBV were classified into five genotypes with Three genotypes different from vaccine strains, vaccine protection test showed that Massachusetts type vaccine could not protect chickens against challenge with this three new genotypes.